Implementasi Kebijakan Pengadaan Barang/Jasa Secara Elektronik Di Kabupaten Kepahiang - fitriani, sumi (Jurnal Governance dan Administrasi Publik, 2021)
The discussion of the implementation of the procurement of goods / services electronically in the Kepahiang Regency is still relatively new. This study uses a qualitative approach deskriptif analysis and data collection is done by in-depth interviews, observation and documentation. The study shows that the SKPD Kepahiang of Regency still experiencing delays in presenting RUP. LPSE Kepahiang of Regency provide services and assistance form for the parties who have a desire explanations related to the procurement of goods / services electronically at any time. Delay in delivery RUP is not in line with the basic principles of procurement of goods / services as proposed by Hardjowijono and Muhammad (2008), one of which is the principle of transparency in the procurement of goods / services is the provision of detailed information on the rules of the procurement of goods and services to all potential providers goods / services and the public interest. Moreover, the delay of views RUP has been at odds with the President of the Republic of Indonesia Regulation Number 54 of 2010 Concerning the Procurement of Goods / services of the Government amendments, stating that the PA / KPA must announce broadly Public Procurement Plan at least at the regional website.